Shell hardening of unalloyed steel cylinders by high speed quenching. (December 2014) - Frerichs, F.; Lübben, T.; Hoffmann, F.; Zoch, H.-W.
Abstract : Kobasko et al. have primarily shown that rapid water quenching can create compressive residual stresses near the surface and thereby a significant increase in the fatigue-limit (Intensive Quenching). Such processes result in an increase in hardness. Depending on steel grade, dimensions of the component and quenching intensity through hardening or only shell hardening will result. In this work, shell hardening processes were investigated in a more detailed manner for cylinders made of two different unalloyed steels. The goal of the work was discovering the general requirements to reach, on the one hand, a sufficient surface hardness paired with a non-through hardened hardening profile. On the other hand, compressive residual stresses in the near surface area should be as high as possible to achieve huge lifetime cycles for the heat treated work pieces. The experiments were carried out with a device that was especially developed for high speed quenching. As a quenching medium only tap water or water with 10% salt were used. It was shown that with this equipment very high heat transfer coefficients up to 50 000 W m −2 K −1 can be reached. Within the experimental design, cylinder made out of C35 and C56E2 with diameters between 25 and 43 mm were quenched with heat transfer coefficients in the range of 20 000 to 50 000 W m −2 K −1 . The quenching results were characterised by measuring the microstructure, the hardness and the residual stresses. The experiments show that compressive stresses in the near surface area of 1200 MPa can be achieved.